Eficácia e segurança da implantação de hipotermia cerebral exclusiva por meio do uso de cateter nasofaríngeo em seres humanos para o tratamento de traumatismo cranioencefálico grave - estudo de fase I - Ferreira, Raphael Einsfeld Simoes [UNIFESP] (2019)
Objective: The objective was to determine whether a novel nasopharyngeal catheter could be used, as a new strategy, to cool the human brain (reduction of at least 2 °C) after traumatic brain injury, and the secondary objective was to assess the local and systemic effects of this therapeutic strategy. Methods: This was a non-randomized, interventional clinical trial that involved five patients with severe traumatic brain injury. The intervention consisted of inducing and maintaining selective brain cooling for 24h by positioning a catheter in the nasopharynx and circulating cold water inside the catheter in a closed loop arrangement. Core temperature was maintained greater than 35 °C using counter-warming strategies. Results: In all study participants, a brain temperature reduction of ≥ 2 °C was achieved. The mean brain temperature reduction from baseline was 2.5 ± 0.9°C (p = .04, 95% confidence interval). The mean systemic temperature was 37.3 ± 1.1 °C at baseline and 36.0 ± 0.8 °C during the intervention. The mean difference between the brain temperature and the systemic temperature during intervention was -1.2 ± 0.8 °C (p = .04). The intervention was well tolerated with no significant changes observed in the hemodynamic parameters. No relevant variations in intracranial pressure and transcranial Doppler were observed. The laboratory results underwent no major changes, aside from the K+ levels and blood counts. The K+ levels significantly varied (p = .04); however, the variation was within the normal range. Only one patient experienced an event of mild localized and superficial nasal discoloration, which was re-evaluated on the seventh day and indicated complete recovery. Conclusion: The results suggest that our non-invasive method for selective brain cooling, using a novel nasopharyngeal catheter, was effective and safe for use in humans.